Experimental study on compressive strength of sediment brick masonry - Woen, E.L. (American Institute of Physics Inc., 2018)
The effects of pre-wetted unit bricks, mortar type and slenderness ratio of prisms on the compressive strength and failure mode of newly developed sediment brick have been evaluated and compared to clay brick and cement-sand bricks. The results show that pre-wetted sediment brick masonry exhibits higher compressive strength of up to 20 compared to the dry sediment masonry. Using cement-lime mortar leads to lower compressive strength compared to cement mortar. However, the sediment brick masonry with the cement lime mortar exhibit higher compressive strength in comparison with cement mortar masonry. More of diagonal shear cracks have been observed in the failure mode of the sediment bricks masonry compared to clay and cement-sand bricks masonry that show mostly vertical cracks and crushing. The sediment unit bricks display compressive strength in between clay and cement-sand bricks. Â© 2018 Author(s).